The Risk Factors Associated with HIV Infection among Attendees at Edelweiss Clinic, Dr. Sardjito Hospital, Yogyakarta - Nurul Nadiah Binti Muhamad Shaidi; Yanri Wijayanti Subroto; Sumardi Sumardi (Tropical Medicine Journal, 2012)
ABSTRACTIntroduction: The majority of human immunodeficiency virus (HIV) infections in Indonesia are transmitted by using contaminated injecting equipment, unprotected paid sex, and unsafe sex between men. The spread of HIV is further exacerbated by several factors, including a widespread commercial sex industry, high prevalence rates of sexually transmitted infections (STIs) and its insufficient clinical services, as well as the very low rate of condom use. However, data regarding the risk factors of HIV infection in Yogyakarta is limited.Objectives: The aim of this study was to identify the risk factors of HIV infection among attendees tested for HIV at Edelweiss Clinic, Dr. Sardjito Hospital, Yogyakarta in 2008.Methods: This study was a cross-sectional study involving 58 participants who divided into HIV-positive and HIV-negative groups. Demographic and risk factor data were collected from medical records. Data were analyzed using Chi-square test.Results: Among HIV-positive patients, 65.4% were sexually active and 19.2% were drug users. Although it was not statistically significant, sexually active might be associated with HIV infection. Among sexually active HIV-positive individuals, 41.2% had multiple partners. However, its association with the disease was weak (r = 0.115). Injecting drug users (IDUs) had higher risk getting HIV infection (r = 0.115) compare to sexually active individuals (r = 0.000). Anal sex (r = 0.038) had a weak association with HIV-positive status.Conclusion: Sexually active was a risk factor of HIV infection among attendees tested for HIV at Edelweiss Clinic. The chance of virus transmission was higher among the IDUs. Keywords: HIV, risk factor, sexually active, injecting drug users